Khilafah Dalam Teks Al-Qur’an dan Konteks Historis Islam - Nurrosidah, Lulukita; Muhtasorul Muzanni Ahmad; Ummu Melliya Adiba (STAI Terpadu Yogyakarta, 2024)
The study of the Caliphate in the Qur'anic Text and the Historical Context of Islam is always interesting to discuss today. Both from a historical perspective, Islamic politics and even interpretation of the Koran. In the perspective of the Qur'an, the State as an institution of power is needed by Islam as an effective instrument to realize its teachings in a historical context to ensure the continuity of religion and the benefit of the world (its people). Therefore, the author reviews the Khilafah verses in the Qur'an contained in Surah Al-Baqarah verse 30, Al-A'raf verse 69, an-Naml verse 62. This effort needs to be made to find explanations for several expert. This research uses a descriptive analysis approach, including library research. So that we get the results of four political principles, structure and the system of the Khilafah State in Islam.